PENGUATAN PEDULI LINGKUNGAN MELALUI MEDIA CERITA RAKYAT DI KECAMATAN NGAWI SEBAGAI PEMBELAJARAN TEKS FIKSI - Vinsca Sabrina Claudia; Sarwiji Suwandi; Nugraheni Eko Wardani (STKIP PGRI SUMENEP, 2021)
Text learning provided by students at the Junior High School level (JHS) is in the form of fiction and non-fiction texts. This study focuses on fictional texts about folklore based on local wisdom for class VIII. The taking of local wisdom folklore is motivated by the element of caring for nature as a strengthening of character values ​​to realize the goals of character education found in the National Education System. Thus, educators try to provide folklore media as a means of learning literary texts, especially fiction texts. Thus, this study aims to explain and describe (1) character building through folklore media; (2) Folklore media make use of local wisdom stories in Ngawi sub-district, Ngawi district, and (3) the application of environmental values ​​in folklore in Ngawi sub-district, Ngawi district. The method used in this research is descriptive qualitative. The results showed that (1) folklore media can provide educational facilities as well as teaching character education in the form of environmental care values; (2) Folklore in Ngawi sub-district as a medium to motivate students to explain concern for the surrounding environment, and (3) an alternative learning media facility for creative and innovative fictional text material